Arterial hypertension in hypothyrosis: severity and state of renin-aldosteron system - G. B. Selivanova; P. Kh. Dzhanashiya (Российский кардиологический журнал)
A survey on arterial hypertension (AH) severity and renin-angiotensin-aldosteron system activity in primary hypothyrosis was performed. Itwas demonstrated that such patients had II and III Stage of AH, with severity progression in older age, and more pronounced abnormalities of 24-hour blood pressure profile at advanced AH stages. Plasma renin activity and aldosteron concentration were within normal range, but lower than the same parameters in essential arterial hypertension.